Escrita de mulheres idosas: identidade e empoderamento - Machado, Marianne Christina Campos (2016)
The research titled Writing older women: identity and empowerment sought to emphasize the need for greater encouragement of writing practice, taking – in to account not only the benefits that this practice can bring health, but also realize the dialogical character that language features. This older women know the importance of his writings, given that all have raw material to produce and establish its interaction with the world. High light and encourage the production of women who have featured in literary circles is also recognized that the elderly is an accumulation of many experiences that deserve to be recorded, and show that as women we are, we can and should be authors and writers of our own lives throughout our existence, as the bahian poet Anna Autran (1871) stated, when comparing writing with the seam, the seam fatigue the penalty gives breadwinner; the first is forgotten, and the second will always be remembered. The methodology is based on qualitative research through document analysis; using the methodological approach of oral history, through semistructured interviews. In the theoretical framework, include: Bakhtin (2003.2006), León (2000), Hall (1997.2006), Perrot (1998, 2005, 2008), among others. The study had as subjects four former students who joined the project University of the Third Age - UNITI, the Federal University of Maranhão - UFMA in 2002, 2010 and 2015. Therefore, we understand that education, as a right of all people, through the practice of writing, further enriches the process of construction and authorship of many women in old age. So at this stage they seek to solidify values and concepts, with what really has to offer, which are the lived experiences and remade every day as subjects of this story. Thus, this study highlight the importance of universities of the third age to the discovery of new identities and the empowerment of older women through writing practice.